A UML Profile for Fuzzy Multidimensional Data Models - Rodriguez, Iván (2010)
Over the last several years, multidimensional data modeling has had several proposals for its formalisation; on the other hand, the incorporation of fuzzy logic in databases has increased the need to represent uncertainty. However, to our knowledge, so far projects in both areas have not been developed. This paper suggests joining those two needs to create a solution; proposing a UML profile oriented to design multidimensional data models with the presence of fuzzy elements.